Students’ Ability in Writing Opinion Essay Using Writing Process Method and a Story Based on Adab Education - Hasnawati Hasnawati; E Mujahiddin; Hendri Tanjung (STAI Hubbulwathan Duri, 2023)
A Good writing is determined by some things, one of which is its process. This study aimed at finding out the influence of the writing process method and a story based on Adab education on the student’s ability to write an opinion essay. The design of this research is mixed method research. The research population was eight classes of undergraduate students in semester 3 of the English Education Department of Teacher Training and Education Faculty in the academic year 2019/2020. The research sample was 37 students that were purposively chosen. The instruments used were a pretest and a posttest. The findings showed that the average posttest score for the experimental class (71.0) was two points higher than the score for the control class (69.0). The results of calculating the difference between the experimental class's posttest and pretest values, a value of 24, were obtained. In contrast, in the control class, a value of 26 was obtained as the result of calculating the difference between the posttest and pretest values. The difference between the two results was -2. Based on that, the conclusion was that the influence of the writing process method and a story based on Adab's education was insignificant. In other words, the writing process method and a story based on Adab education were similarly good in improving students' competence in writing an opinion essay. The findings suggest the necessity of doing or implementing the writing process and a story based on Adab’s education if students hope to have good English writing particularly an opinion essay.